Enzyme systems activity and connective tissue metabolism as pathogenetic factors of spinal stenosis (literature review) - L. V. Rodionova (Scientific Сentre for Family Health and Human Reproduction Problems, 2015)
A characteristic feature of stenosis process of the spinal canal is the destruction of elastin and fibrosis of the extracellular matrix, as well as hypertrophy and ossification of the ligamentum flavum. Proven participation in these processes of genes CTGF, PDGF-BB, TGF-ß, Il-6, TNF-α, MMPs, TIMPs, etc. Potent inducer of extracellular deposition of collagen in hypertrophies ligamentum flavum is TGF-ß; GDF-5 has osteogenic effect, increases the activity of alkaline phosphatase and the expression of osteocalcin, induces mineralization; FGFR3 gene expression contributes to the closure of synchondroses and merging of centers of ossification, contributing to excess synthesis of bone tissue, etc. Local or a systemic effect on the expression of these genes may be effective to prevent progression of the disease. Predisposition to stenosis and responsiveness to therapy is genetically determined and is expressed in individual differences in metabolic status. A very important role in the pathobiochemistry of connective tissue are the processes of acetylation by regulating the expression of essential genes that affects all intracellular processes and especially in the fibrogenesis. An imbalance of acetylation may lead to excessive synthesis of collagen, accelerating the growth of connective tissue, disruption of lipid homeostasis. Therefore, it is relevant as the definition of NAT2 polymorphism and phenotypic identification of the rate of acetylation in the population, as well as finding relationships with various pathological processes. Meaningful impact on the processes of acetylation may contribute to the sanogenesis. The information presented in the review is important for the formation of a new perspective on the pathogenesis of stenosis process in the spinal canal and can contribute to the development of new approaches to treatment.